Graham Pryor, Sarah Jones and Angus Whyte, editors (2014) Delivering Research Data Management Services: Fundamentals of good practice. London: Facet. Issue 4 (19th August 2014) - Cox, Andrew; Sicilia, Miguel-Angel; Eyre, John
<x content-type="archive" xml:space="preserve">Abstract</x>